EMPLOYEE ENGAGEMENT AS THE KEY TO OPTIMIZING PERFORMANCE: UNDERSTANDING THE IMPACT OF POWER DISTANCE AT CV MEGA MENDUNG STELL - Rezeki, Fitri; Mardiputra, Hamzah Muhammad; Supriyanto, Supriyanto; Fahamsyah, Mohammad Hatta (Jurnal Apresiasi Ekonomi, 2024)
Human resources (HR) play a crucial role in achieving organizational goals. Employee engagement is expected to enhance performance by deepening the understanding and implementation of job functions. Both qualitative and quantitative employee performance are essential for a company's success, as they directly impact outcomes. At CV Mega Mendung Stell, declining employee performance has negatively affected profitability. Strong employee motivation is critical for maintaining a competitive edge, as engaged employees typically exhibit higher performance levels and stronger attachment to their work and company. Research shows that power distance within an organization—measuring the extent to which power differences are accepted and communicated—has a significant impact on employee performance. High power distance can lower motivation, while low power distance can place excessive pressure on employees. Effective work engagement can manage this balance, fostering an environment that promotes engagement and efficient decision-making, thereby improving overall organizational effectiveness. This study aims to explore the impact of employee engagement on performance at CV Mega Mendung Stell, providing insights to improve HR management and organizational performance. Keywords: Employee Engagement , Employe Performance , Power Distance